New fundamental rights within the scope of UNASUR: Analysis of the Brazil and Venezuela Agendas in the light of the Right to Peace - Pulzatto Peruzzo, Pedro; Spada, Arthur Ciciliati [UNESP] (Centro de Ensino Unificado de Brasilia, 2018)
The present article introduces an analysis of the fundamental right to peace within the Union of South American Nations (UNASUR) Through an interdisciplinary study conducted between Law and International Relations, the objective of this study was to evaluate the applicability of this right in the political and normative construction process of UNASUR and its South American Defense Council (CDS) from the agendas of Brazil and Venezuela. We consider as a hypothesis that peace is still an objective of difficult reach in the region, more due to the serious situation of internal violence than due to possible external conflicts since the continent has no declared warlike conflict. This situation requires the establishment of common political guidelines that, based on the new movements of globalization and transnationality, seek to consider in the analysis of how these differences are related to the regional leadership role and reflect on the normative set of the organization.
Novos direitos fundamentais no âmbito da UNASUL: Análise das agendas de Brasil e Venezuela à luz do direito à paz
Keywords: Brazil; Fundamental right to peace; International legal cooperation; UNASUR; Venezuela